Longitudinal changes in serum vitamin D binding protein and free 25-hydroxyvitamin D in a multiracial cohort of pregnant adolescents. Issue 186 (February 2019) - Best, Cora M.; Pressman, Eva K.; Queenan, Ruth Anne; Cooper, Elizabeth; O'Brien, Kimberly O.
Highlights: We directly measured serum free 25(OH)D and DBP in pregnant adolescents. Longitudinal increase in DBP was associated with modest decrease in free 25(OH)D. Percent free 25(OH)D was slightly greater in African Americans compared with Whites. Total 25(OH)D rather than free was a stronger correlate of PTH and 24, 25(OH)2 D. Abstract: Serum free 25-hydroxyvitamin D (25(OH)D) rather than total 25(OH)D may better indicate vitamin D status during pregnancy given the pregnancy-associated increase in serum vitamin D binding protein (DBP) concentration. Our aims were to assess changes in DBP and free 25(OH)D across gestation and to determine whether free compared with total 25(OH)D more strongly correlates with markers of vitamin D and calcium metabolism during pregnancy. This ancillary study included 58 pregnant adolescents (53% African American, 47% White) who completed a vitamin D3 supplementation study in Rochester, NY. Blood was collected at entry, mid-study, and delivery (median 17, 29, and 40 weeks' gestation). Mixed-effects regression was used to test for differences in DBP, directly measured free 25(OH)D, and other serum markers by study visit and race. Free and total 25(OH)D were evaluated in relation to serum PTH, 1, 25(OH)2 D, 24, 25(OH)2 D, and calcium. The mean DBP concentration was above nonpregnant reference values at entry and increased across gestation ( P < 0.0001). Total 25(OH)D explained most of the variance in free 25(OH)D ( r ≥ 0.67; P < 0.0001). Holding total 25(OH)D constant, each 100 mg/L increase in DBP was associated with a 0.4 pg/mL decrease in free 25(OH)D ( P < 0.01). The percent free 25(OH)D was inversely related to both DBP and total 25(OH)D at each visit. Regardless of race or visit, total 25(OH)D was a stronger correlate of PTH, 1, 25(OH)2 D, and 24, 25(OH)2 D, and neither total nor free 25(OH)D was related to serum calcium. African Americans had lower total 25(OH)D ( P < 0.0001), but free 25(OH)D did not significantly differ by race ( P = 0.2). In pregnant adolescents, DBP concentration was elevated and inversely associated with percent free 25(OH)D, but measured free 25(OH)D provided no advantage over total 25(OH)D as a predictor of PTH, 1, 25(OH)2 D, 24, 25(OH)2 D, or calcium. The clinical relevance of the small racial difference in percent free 25(OH)D requires further investigation.